Micro-Poluentes Emergentes de Origem Farmacêutica em Matrizes Aquosas do Brasil – Uma Revisão Sistemática - Boger, Beatriz; Tonin, Fernanda Stumpf; Zamora, Patricio Guillermo Peralta; Wagner, Ricardo; Gomes, Eliane Carneiro (Ciência e Natura, 2015)
The increasing concern about the environment and population health leads to further research on water quality monitoring in Brazil, mainly in terms of the presence of pharmaceutical chemicals compounds residues. Objective: To extensile review literature studies that quantifies micro emerging pollutants of pharmaceutical compounds in Brazilian waters in order to gather evidences and provide information about the quality of water in the country. Methods: A systematic review was conducted in electronic databases PubMed, Science Direct, Scopus and SciELO, along with manual search to identify studies on drug detection in waters surface or from sewage in Brazil, between years 1999 and 2014. Only studies in English and Portuguese and those who answered the inclusion criteria were selected. Results: A total of 1126 studies were inicially identified and after screening and selection 11 of them met the inclusion criteria three studies were added from the manual search. In Brazil, unlike what happens in European countries and in the United States, the results showed that there are few studies on the evaluation of water quality related with micro-pollutants of pharmaceutical origin.